Study on Hydrate Risk in the Water Drainage Pipeline for Offshore Natural Gas Hydrate Pilot Production - Guimin, Yu; Hao, Jin; Qingwen, Kong (Frontiers in Earth Science, 2022)
Hydrate plug in the drainage line is a serious flow assurance problem for the pilot production of offshore natural gas hydrates. Current researches focus on the hydrate deposition in the annular flow and the oil-dominated system. The multiphase flow system in the drainage line is a water-dominated system which is normally a bubbly flow. In this work, a new model is developed to study the temperature and pressure field in the drainage line considering that the flow pattern is bubbly flow. Combining with the methane hydrate phase equilibrium curve, the hydrate formation region in the drainage line can be established. The hydrate formation region is enlarged with the ESP pressure increasing and the water production rate decreasing, since the ESP can supply extra pressures in the drainage line and the heat transfer phenomenon is enhanced between the drainage line and environment under the low water production rate condition. The model pointed out that the risk of hydrate formation rises up as the hydrate concentration increasing beyond 6%. This study can lay a theoretical foundation for the efficient prevention of gas hydrates in the drainage line during offshore natural gas hydrate pilot or long-term production.